Butyrate's role in human health and the current progress towards its clinical application to treat gastrointestinal disease. Issue 2 (February 2023) - Hodgkinson, Kendra; El Abbar, Faiha; Dobranowski, Peter; Manoogian, Juliana; Butcher, James; Figeys, Daniel; Mack, David; Stintzi, Alain
Summary: Butyrate is a key energy source for colonocytes and is produced by the gut microbiota through fermentation of dietary fiber. Butyrate is a histone deacetylase inhibitor and also signals through three G-protein coupled receptors. It is clear that butyrate has an important role in gastrointestinal health and that butyrate levels can impact both host and microbial functions that are intimately coupled with each other. Maintaining optimal butyrate levels improves gastrointestinal health in animal models by supporting colonocyte function, decreasing inflammation, maintaining the gut barrier, and promoting a healthy microbiome. Butyrate has also shown protective actions in the context of intestinal diseases such as inflammatory bowel disease, graft-versus-host disease of the gastrointestinal tract, and colon cancer, whereas lower levels of butyrate and/or the microbes which are responsible for producing this metabolite are associated with disease and poorer health outcomes. However, clinical efforts to increase butyrate levels in humans and reverse these negative outcomes have generated mixed results. This article discusses our current understanding of the molecular mechanisms of butyrate action with a focus on the gastrointestinal system, the links between host and microbial factors, and the efforts that are currently underway to apply the knowledge gained from the bench to bedside.